Spin-state crossover in photo-catalyzed nitrile dihydroboration via Mn-thiolate cooperation. Issue 42 (20th October 2022) - Elsby, Matthew R.; Oh, Changjin; Son, Mina; Kim, Scott Y. H.; Baik, Mu-Hyun; Baker, R. Tom
Abstract : The role of a phosphine-free SNS-pincer ligand in metal–ligand cooperative hydroboration catalysis was investigated. The bifunctional thiolate donor and spin-state change to high-spin Mn are crucial to accessing low-energy activation barriers. Abstract : The role of S-donors in ligand-assisted catalysis using first-row metals has not been broadly investigated. Herein is described a combined experimental and computational mechanistic study of the dihydroboration of nitriles with pinacolborane (HBpin) catalyzed by the Mn(i ) complex, Mn(κ 3 -S Me NS)(CO)3, that features thioether, imine, and thiolate donors. Mechanistic studies revealed that catalysis requires the presence of UV light to enter and remain in the catalytic cycle and evidence is presented for loss of two CO ligands. Stoichiometric reactions showed that HBpin reduces the imine NC of the ligand backbone in the absence of nitrile, forming an inactive off-cycle by-product. DFT calculations showed that the bifunctional thiolate donor, coordinative flexibility of the S Me NS ligand, and access to an open-shell intermediate are all crucuial to accessing low-energy intermediates during catalysis.